Comportamiento preliminar de la variedad de algodón NuOpal en diferentes arreglos espaciales en el distrito de Gral. Artigas (Journal on studies and research of academic knowledge, 2014)
This research was carried out during 2013/2014 crop season on the farm of Mr. Aquiles Acuña, located at Km 28. Ruta VII district of Gral. Artigas to determine the spatial arrangement with higher yield potential of Nu Opal cotton variety under the Varkky ung A agroecological conditions of Gral Artigas district randomized block design with a plot split arrangement were used for eight treatments and four replications were main plots was used as distance between plants (10 and 20 cm) and subplots as row spacing ( 38, 50, 75 and 100 cm). of flowering The trial was established in october 2014. The variables evaluated were begining of plant height, number of ball number of fruiting branches weight of seed cotton and yield of seed cotton per hectare Results showed that the spatial arrangements used did not affect the expression of flowering and weight of seed conton contrast, significant differences (P
Keywords: Gossipmentum; variety NuOpal; narrow row; between rows and plants